2016
DOI: 10.1152/ajpheart.00041.2016
|View full text |Cite
|
Sign up to set email alerts
|

Discordant signaling and autophagy response to fasting in hearts of obese mice: Implications for ischemia tolerance

Abstract: Autophagy is regulated by nutrient and energy status and plays an adaptive role during nutrient deprivation and ischemic stress. Metabolic syndrome (MetS) is a hypernutritive state characterized by obesity, dyslipidemia, elevated fasting blood glucose levels, and insulin resistance. It has also been associated with impaired autophagic flux and larger-sized infarcts. We hypothesized that diet-induced obesity (DIO) affects nutrient sensing, explaining the observed cardiac impaired autophagy. We subjected male fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
(49 reference statements)
6
19
0
Order By: Relevance
“…This is different from the diet-induced obese (DIO) mouse model, where the defect in cardiac autophagy appears to be caused by an impairment in lysosomal clearance [37, 38, 40]. The basis for this difference is not entirely known but may involve the induction of mTOR signaling in ( ob/ob ) hearts versus no change or a reduction in this pathway in DIO mice [38, 40]. However, other DIO studies with longer durations and higher fat content in the diet have reported higher Akt and mTOR signaling in the heart [16, 37], similar to what we observed in ( ob/ob ) hearts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is different from the diet-induced obese (DIO) mouse model, where the defect in cardiac autophagy appears to be caused by an impairment in lysosomal clearance [37, 38, 40]. The basis for this difference is not entirely known but may involve the induction of mTOR signaling in ( ob/ob ) hearts versus no change or a reduction in this pathway in DIO mice [38, 40]. However, other DIO studies with longer durations and higher fat content in the diet have reported higher Akt and mTOR signaling in the heart [16, 37], similar to what we observed in ( ob/ob ) hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Using ( ob/ob ) mice we showed that autophagic flux is impaired in the heart and this is due to alterations in autophagosome formation rather than a defect in their clearance by lysosomes. This is different from the diet-induced obese (DIO) mouse model, where the defect in cardiac autophagy appears to be caused by an impairment in lysosomal clearance [37, 38, 40]. The basis for this difference is not entirely known but may involve the induction of mTOR signaling in ( ob/ob ) hearts versus no change or a reduction in this pathway in DIO mice [38, 40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…124 In contrast, a similar type 2 diabetic patient cohort exhibits decreased cardiac Atg5 protein expression, and no change in LC3. 131 The autophagic response to fasting-and ischemia-induced metabolic stress is blunted in obese insulin resistant mice, 59, 128 which may underlie exacerbated ischemic injury evident in diabetes. Glycophagy may play an important role in diabetic cardiomyocytes, coincident with disturbances in glycogen metabolism.…”
Section: Cardiopathology Involvementmentioning
confidence: 99%
“…Similarly, time-restricted feeding (8 h per day) results in a period of fasting and can protect mice against the ill effects of a high-fat diet 252 . A high-fat diet has been shown to impair autophagy 253,254 and reduce ischaemic tolerance 255 , underscoring the importance of intact autophagic flux in cardioprotection. Like caloric restriction and intermittent fasting, exercise upregulates autophagy and is associated with cardioprotection 256,257 .…”
Section: Autophagy As a New Therapeutic Targetmentioning
confidence: 99%